Global energy transformation : a roadmap to 2050 (International Renewable Energy Agency, 2019)
Increased use of renewable energy, combined with intensified electrification, could prove decisive for the world to meet key climate goals by 2050. This study from the International Renewable Energy Agency (IRENA) highlights immediately deployable, cost-effective options for countries to fulfil climate commitments and limit the rise of global temperatures. The envisaged energy transformation would also reduce net costs and bring significant socio-economic benefits, such as increased economic growth, job creation and overall welfare gains. The report - the second under the Global Energy Transformation banner - expands IRENA's comprehensive roadmap, which examines technology pathways and policy implications to ensure a sustainable energy future. Ramping up electricity to over half of the global energy mix (up from one-fifth currently) in combination with renewables would reduce the use of fossil fuels, responsible for most greenhouse-gas emissions.